2009
DOI: 10.1525/sop.2009.52.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Pluralistic Ignorance among Assembled Peers

Abstract: Sociologists have long been interested in pluralistic ignorance—situations where a majority of individuals assume that most of their peers think differently than themselves when, in fact, their attitudes are similar. Recently, sociologists have suggested that pluralistic ignorance is especially likely to occur when peers are gathered together and may explain why group members often refrain from discussing their ultimate concerns with each other. However, researchers have not indicated what factors besides phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 24 publications
2
22
0
Order By: Relevance
“…Similar to the study recently reported by Kroshus et al (2015) who found that the players who though that 'most athletes' would report concussions, were themselves the least likely to underreport their own head injuries during the season; the findings from this study may also involve the phenomena of what has been termed 'pluralistic ignorance' (Grant, O'neil, & Stephens, 2009). As proposed in the sociology literature, pluralistic ignorance refers to where the majority of individuals perceive that most of their peers think differently to themselves when, actually, individual attitudes are similar.…”
Section: Limitations Of the Study And Considerations For Further Ressupporting
confidence: 88%
See 1 more Smart Citation
“…Similar to the study recently reported by Kroshus et al (2015) who found that the players who though that 'most athletes' would report concussions, were themselves the least likely to underreport their own head injuries during the season; the findings from this study may also involve the phenomena of what has been termed 'pluralistic ignorance' (Grant, O'neil, & Stephens, 2009). As proposed in the sociology literature, pluralistic ignorance refers to where the majority of individuals perceive that most of their peers think differently to themselves when, actually, individual attitudes are similar.…”
Section: Limitations Of the Study And Considerations For Further Ressupporting
confidence: 88%
“…In other words, we did not ascertain if individuals in our cohort felt that others thought similarly to them. Further, given the prominence of the issue of sports concussion in recent years, examination is required to investigate if interpersonal networks and socio-technical conditions (such as social media) can combine to produce pluralistic ignorance (Grant et al, 2009) and misperceptions of students about their peers' attitudes and knowledge.…”
Section: Limitations Of the Study And Considerations For Further Resmentioning
confidence: 99%
“…If receiving feedback about the progress of quality improvement initiatives is associated with stronger spiritual climate scores, then perhaps future interventions could target spiritual climate improvements and discussions (feedback) with healthcare workers. While specific interventions to augment spiritual climate in healthcare workers have not been reported in the literature to date, Grant et al reported that nurses who attended meetings where spirituality was frequently discussed were much more cognizant of their colleagues’ desire to express and talk openly about spirituality [ 4 ]. Spiritual climate was related to teamwork climate in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas prior research had focused almost exclusively on religious affiliations, practices and values , subsequent studies were primarily concerned with the personal meanings that people attached to spirituality. Workplace spirituality was defined by Ashmos and Duchon [ 3 ], as “the recognition that employees have an inner life that nourishes and is nourished by meaningful work that takes place in the context of community” [ 4 ]. Organizations that embrace workplace spirituality by encouraging the respectful expression of diverse spiritual views have staff who report bringing more of their “complete selves” to work [ 2 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Refinement of causal conditions is done by excluding all the irrelevant conditions that do not lead to the outcome due to contextual reasons. Such measures ensure parsimony in qualitative comparative analysis and enable the researchers to closely reexamine the causal conditions (Grant, O'Neil and Stephens, 2009). Later for empirical analysis through QCA, these recipes are organized in the form of truth tables.…”
Section: Configurations or "Recipes"mentioning
confidence: 99%